Evaluation of the effects of laparoscopic adjustable gastric banding versus laparoscopic sleeve gastrectomy on weight loss - Gündoğdu, Emre; Bilgiç, Celal İsmail and Moran, Münevver and Güldoğan, Cem Emir and Dilektaşlı, Evren and Özmen, Mehmet Mahir (The European Research Journal, 2020)
Objectives: Obesity has become one of the most serious and ever increasing health problems of our times. Diet, exercise and medical treatment have proven to be insufficient. Operations such as laparoscopic adjustable gastric banding (LAGB) and laparoscopic sleeve gastrectomy (LSG) have gained popularity. The purpose of this study is to conduct a retrospective comparative analysis of the clinical results gained from patients treated with LSG and LAGB due to morbid obesity. Methods: The patients included in the study were selected among those who were diagnosed with morbid obesity and were operated with LAGB (n = 55) and LSG (n = 52) from May 2007 to December 2012. Both groups were compared in terms of the demographic characteristics, preoperative and postoperative conditions. Results: The groups were similar in terms of age, sex and BMI. In the 6th month, there was a notable loss of appetite in the LSG group patients compared to the LAGB patients (69.2% vs. 23.6%, p < 0.001). The rate of excess weight loss in the LAGB group was 23.93% ± 7.98% and 31.7% ± 7.49% in the LSG group in the postoperative 6th months (p = 0.002). The rate of excess weight loss was 45.36% ± 10.92% in the LAGB group and 60.3% ± 9.81% in the LSG group in the postoperative 12th months (p ˂ 0.001). Conclusions: When the two surgical operations for morbid obesity are compared LSG is found to be a more successful method in terms of body weight loss. Nevertheless, longer hospitalization can be associated with the technically more complicated nature of the operation and the fact that it requires resection.